1999
DOI: 10.1046/j.1365-294x.1999.00605.x
|View full text |Cite
|
Sign up to set email alerts
|

Features of DNA fragments obtained by random amplified polymorphic DNA (RAPD) assays

Abstract: Random amplified polymorphic DNA (RAPD) fragments were prepared from samples of Calonectris diomedea (Cory's shearwater, Aves) and Haemonchus contortus (Nematoda) DNA by polymerase chain reaction (PCR) using decamers containing two restriction enzyme sites as primers. Six of 19 studied RAPD fragments probably originated from traces of commensal microorganisms. Many rearranged fragments, absent in the original genomic DNA, were synthesized and amplified during the processing of all the DNA samples, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 9 publications
0
34
1
1
Order By: Relevance
“…It has been shown that RAPD markers may have low reproducibility (Pérez et al, 1998;Rabouam et al, 1999, but see Ramos et al (2008)), and previous results concerning levels of variability and inferred recombination in S. troendelagicum are therefore difficult to interpret with confidence. The aim of this study is to learn more about the evolutionary history of this species, more specifically to (1) determine which of the parental taxa are maternal and paternal progenitors, respectively; (2) quantify patterns of genetic variability and structuring in natural populations of S. troendelagicum and the parental species using variable markers with high reproducibility; (3) test the hypothesis that the species originated multiple times; (4) quantify historical parameters, most importantly time since speciation event(s), to determine whether the species likely originated in central Norway or whether it immigrated after the last ice age; and finally, (5) make suggestions concerning the continued preservation of S. troendelagicum.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that RAPD markers may have low reproducibility (Pérez et al, 1998;Rabouam et al, 1999, but see Ramos et al (2008)), and previous results concerning levels of variability and inferred recombination in S. troendelagicum are therefore difficult to interpret with confidence. The aim of this study is to learn more about the evolutionary history of this species, more specifically to (1) determine which of the parental taxa are maternal and paternal progenitors, respectively; (2) quantify patterns of genetic variability and structuring in natural populations of S. troendelagicum and the parental species using variable markers with high reproducibility; (3) test the hypothesis that the species originated multiple times; (4) quantify historical parameters, most importantly time since speciation event(s), to determine whether the species likely originated in central Norway or whether it immigrated after the last ice age; and finally, (5) make suggestions concerning the continued preservation of S. troendelagicum.…”
Section: Introductionmentioning
confidence: 99%
“…esterase) on DNA during the extraction stage. Rabouam et al (1999) attributed artefactual RAPD polymorphism to the presence of commensal organisms and fragment rearrangements during PCR amplifi cation. W = water; A = alcohol; the number of bee corresponds to its position on the gel; fragment name is represented by number of band (ex.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these techniques have been widely employed in genetic analysis of a variety of adult insects (Carvalho & Vieira 2001, Watts et al 2004, Keyghobadi et al 2005, Sofi a et al 2005. However, when total genomic DNA is extracted from adult insect body parts, a worrying aspect of the genetic analysis can be the incidence of spurious DNA due, for instance, to the presence of commensal organisms associated with the material under study (Rabouam et al 1999). In researches involving adult bees, or even adult insects in general, the most frequent sources of such DNA are pollen and microorganisms on the insect integument.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids were purified and sequenced as previously described (Rabouam et al 1999). The 25 sequences reported in this paper appear in the DDBJ/EMBL/GenBank sequence database under accession numbers AJ009223-AJ009247.…”
Section: Pcr Amplifications and Fragment Cloningmentioning
confidence: 99%